DOES THE QUALITY OF SERVICE AND ACCOMMODATION FACILITIES AFFECT THE CONSUMER SATISFACTION? CASE BUNDA HOUSE SYARIAH PADANG - Elva Dona; Dedek Lestaluhu; Indriani, Novia (INQUISITIVE : International Journal of Economic, 2025)
Accommodation is essential for supporting the tourism industry in Padang along with surrounding areas. This study would like to assess how accommodation facilities affect consumer satisfaction at Bunda House Syariah. The population the research projrct surveyed 67 visitors who stayed at Bunda House Syariah throughout 2024. The study identified a substantial positive correlation between service quality and customer satisfaction, meaning that guests at Bunda House Syariah feel comfortable and well-served by the provided services, leading them to make repeat reservations when visiting Padang. On the other hand, the accommodation facility variable was found to be insignificant, which suggests that customers at Bunda House Syariah are already satisfied and find the existing facilities suitable for their needs. Future studies can consider for add other variables that have a more significant impact on customer satisfaction like price perception, Technology Adoption and so on.